CroCA - Cromoterapia e computação afetiva: auxiliando os estados de ansiedade - Muniz, Rafael da Silva; Rodrigues, Rafael Guimarães; Guedes, Gustavo Paiva (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
Anxiety disorders affect a lot of people and can cause feelings of breathlessness, chest pain, sweating, among others. When uncontrolled, anxiety can influence individuals lives in a rather negative way. In Sa˜o Paulo, for example, it is estimated that 12% of the population has had some kind of anxiety disorder. This paper proposes a website in which users write daily texts. This website processes the words in these texts and, if anxiety words are found, the interface color scheme is changed. The theoretical foundation comes from scientific studies that highlight the effect presented by the colors. For example, some colors tend to calm (e.g. blue) while others tend to cause excitation (e.g. red). In this scenario, our proposed website can change, in real time, its interface, providing an user-adapted content. Preliminary results point in a promising direction.